Lung Protection vs. Infection Resolution: Interleukin 10 Suspected of Double-Dealing in COVID-19 - Lindner, Holger A.; Velásquez, Sonia Y.; Thiel, Manfred; Kirschning, Thomas (Frontiers in Immunology, 2021)
The pathological processes by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection that make the virus a major threat to global health are insufficiently understood. Inefficient viral clearance at any stage is a hallmark of coronavirus disease 2019 (COVID-19). Disease severity is associated with increases in peripheral blood cytokines among which interleukin 10 (IL-10) increases particularly early and independent of patient age, which is not seen in active SARS-CoV infection. Here, we consider the known multi-faceted immune regulatory role of IL-10, both in protecting the lung from injury and in defense against infections, as well as its potential cellular source. While the absence of an IL-10 response in SARS is thought to contribute to early deterioration, we suspect IL-10 to protect the lung from early immune-mediated damage and to interfere with viral clearance in COVID-19. This may further both viral spread and poor outcome in many high-risk patients. Identifying the features of the viral genotype, which specifically underlie the different IL-10 dynamics as an etiological endotype and the different viral load kinetics and outcomes as clinical phenotype, may unveil a new immune evasive strategy of SARS-CoV-2.